Criminology Study of Perpetrators of Threats and Defamation Crimes on Social Media Based on ITE Law NO 11 of 2008 - wiranda, aditya nefa; Prasetyoningsih, Nanik (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to analyze Criminological Studies on Perpetrators of Threats and Defamation Crimes on Social Media Based on the ITE Law NO 11 of 2008. Furthermore, this article uses normative legal methods. The research attempts to examine all laws and regulations related to legal issues being researched. Thus, this research will involve an in-depth analysis of Law No. 11 of 2008 concerning Electronic Information and Transactions (UU ITE) and other related regulations and regulations relating to criminalizing perpetrators of crimes of threats and defamation on social media. This research shows that defamation is a detrimental and often disturbing societal act. Various motives and factors can encourage someone to carry out these actions, ranging from personal or emotional motives to power and control. In the digital era, threats and defamation through electronic media are increasingly becoming an urgent problem, with laws such as the ITE Law No. 11 of 2008, which provide a clear legal basis and strict sanctions against perpetrators. The law protects individuals in maintaining their good name and reputation in cyberspace. With heavy criminal sanctions, it is hoped that law enforcement against criminal acts of defamation can be more effective, provide justice for victims, and prevent cases like this in the future.